Assessing the Effect of Social Science Education on Punitive Attitudes - Costelloe, Michael Thomas; Arazan, Christine; Stenger, Madeline (JSSE - Journal of Social Science Education, 2018)
Purpose: One of the most consistent predictors of punitiveness is education, with more educated individuals expressing less punitive sentiments. While much of the earlier research focused on the level of education, some researchers have recently begun to look more closely at the nature of that education such as examining the effect of specific majors on punitiveness. This paper goes even further by also analyzing more broadly the effect of a social science education on punitive attitudes. Methods: This article presents results from an online survey of 4,000 undergraduate students attending a United States’ university. Ordinary least squares analysis is used to examine the effect of majoring in the social sciences on support for punitive criminal justice policies, while controlling for a number of theoretically relevant variables. Findings: We find that more educated students and those majoring in social science disciplines are generally less punitive than their counterparts. If we are to unburden ourselves of the intricately intermingled economic and social costs of mass incarceration, it will require a re-visioning of how we do justice in America. Social scientists can play a crucial role in this regard through focused research and in educating young people to be critical thinkers and thoughtful citizens.